Incidence of prostate and breast cancer in Brazil during the pandemic: What happened? (Research, Society and Development, 2022)
The pandemic of COVID-19 presented a new reality of indexes such as incidence, mortality, prevalence and recurrence for multifactorial reasons, as public health guidelines aiming at social distancing and isolation. This study aims to survey data regarding the incidence of prostate cancer and breast cancer in the pandemic period in Brazil. The research is characterized as an ecological observational quantitative time series, which aims to collect statistical data on the incidence of prostate cancer and breast cancer during the pandemic period in Brazil. The studies occurred in electronic media during the second half of 2021, for data collection the DATASUS panel from the period 2018 to 2021 referring to the 18 months pre and during the pandemic was used. It is observed that in all regions of Brazil, from September 2018 to February 2020 and between March 2020 to August 2021, there was a 62.28% decrease in prostate cancer cases, and within the same regions and periods there was a 16.39% decrease in breast cancer cases. A decrease in the number of diagnosed cases of prostate and breast cancer was found to have a multifactorial origin. The pandemic has hindered or interrupted the accessibility of screening and prevention tests for the diagnosis of both cancers, also revealing future concerns for patients and healthcare providers, such as uncertain data and worse prognosis due to lack of follow-up.